Making homes more accessible for people with mobility impairment: A lived experience perspective. Issue 4 (2nd May 2022) - Goodwin, Isabella; Davis, Elise; Winkler, Di; Douglas, Jacinta; Wellecke, Cornelia; D'Cruz, Kate; Mulherin, Peter; Liddicoat, Stephanie
Abstract: People with mobility impairment have the right to live in accessible housing that meets their needs. Although the Australian National Construction Code for residential housing will be amended to include minimum accessibility standards in September 2022, some states have chosen not to adopt these standards (New South Wales, Western Australia and South Australia). The inclusion of people with lived experience in decisions surrounding accessible housing design is lacking. This study sought the perspective of people with mobility impairment on the most important modifications they would make to the design of their own homes, and the homes of their friends and family, to make them more accessible. An online survey was completed from February to March 2021 by 145 people living in Australia including 112 people with mobility impairment, and 33 family members. Results indicated that 71 per cent of the participants were living in housing that did not fully meet their accessibility needs. Descriptive qualitative analyses demonstrated that commonly reported modifications included a step‐free entrance, wider internal doors and corridors, and level access throughout the home. These modifications would promote social inclusion, functioning, independence and overall quality of life. These results have policy implications for the implementation of accessibility standards in the National Construction Code.